REKAYASA PROSES EKSTRAKSI DAN PENGELOLAHAN BIJI NIKEL: TEKNOLOGI, TANTANGAN, DAN PROSPEK MASA DEPAN - Sahputra, Wahyu Puji; Badia, Bahdin Ahad; Putra, Muhammad Idris; Putra, Fahrizal Cesar; Aji, Angga Asteriasti (Jurnal Multidisipliner Kapalamada, 2025)
Global nickel demand is rapidly increasing in line with the transition to low-carbon technologies, particularly in the electric vehicle battery industry. This study conducts a systematic literature review of 40 publications (2020–2025) on nickel ore extraction technologies, challenges, and sustainable future prospects. About 55% of the studies discuss pyrometallurgy (RKEF, Blast Furnace) with Ni recovery of 90–95%, energy consumption of 5,500–6,500 kWh/t, and CO? emissions of 15–25 t/t Ni. Around 30% examine HPAL, which processes low-grade limonite with lower energy use, high investment (>USD 1 billion), and complex waste management. The remaining 15% focus on bioleaching (75–85% recovery, ~80% lower energy use, though with long processing time) and selective reduction (Fe?O? reduction at 1,100–1,200 °C, 15–20% lower energy consumption, Ni recovery of 90–93%). Challenges include ore mineralogy variation, nickel price fluctuations, and environmental impact. As the world’s top producer (~50% in 2024), Indonesia must optimize downstream policy and sustainability. Future prospects include commercializing alternative technologies and integrating renewable energy to reduce carbon footprint by up to 60%.